2014
DOI: 10.1037/a0036560
|View full text |Cite
|
Sign up to set email alerts
|

Pathological concern: Scale construction, construct validity, and associations with attachment, self-cohesion, and relational entitlement.

Abstract: Based on clinical evidence and theoretical writings on pathological forms of concern and the destructive role they might play in close relationships, we conducted 2 studies aimed at developing and validating the Pathological Concern Questionnaire (PCQ). This scale comprises items tapping a fragile view of the self, as well as a compulsive need to care for others. Findings indicated that all questionnaire items loaded on a single factor of pathological concern, which was significantly associated with egocentric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…This finding converges with a previous study (Shavit & Tolmacz, 2014) which indicated that pathological concern may evolve from an egocentric motivation for caregiving (as a means of obtaining a sense of control, receiving help, or gaining some reward in the future); healthy concern, by contrast, seems to express more altruistic motives.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This finding converges with a previous study (Shavit & Tolmacz, 2014) which indicated that pathological concern may evolve from an egocentric motivation for caregiving (as a means of obtaining a sense of control, receiving help, or gaining some reward in the future); healthy concern, by contrast, seems to express more altruistic motives.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings, however, indicate the existence of a more complex relationship between the three constructs. Individuals high in PC may appear to be deeply interested in the other and in interpersonal relationships; our findings, as well as previous ones (Shavit & Tolmacz, 2014), suggest that this display is nevertheless better understood as a strategy to cope with their fragile sense of self and an attempt to establish a sense of competence through satisfying others' needs at the expense of their own self-needs. In other words, they allegedly employ a selfas-object and other-as-subject form of relationship.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations